Analysis Of Accounting Treatment Of Revenue Based On PSAK No. 23 At Eastparc Hotel - Charles De Deo Sambi Kaki; Ni Made Dewi Damayanti; Susanti, Christina (Klabat Accounting Review, 2025)
Revenue is the main element in financial statements that greatly determines the success and sustainability of an entity's operations, especially in hospitality companies such as hotels. In its preparation, revenue recognition and measurement must refer to generally applicable accounting standards so that financial statements can be presented in a reasonable, relevant, and reliable manner. PSAK No. 23 is the main reference in the accounting treatment of revenue, especially in transactions of the sale of goods, services, and the use of assets by other parties. This study aims to analyze the extent to which Eastparc Hotel implements PSAK No. 23 in its 2024 consolidated financial statements. The method used is a qualitative descriptive analysis based on financial statements and notes on financial statements issued by the company. The results of the analysis show that Eastparc Hotel has implemented PSAK No. 23 consistently and in accordance with standards, both in recognition, measurement, recording, reporting, and revenue disclosure. This reflects a high level of compliance with financial accounting standards and transparency in the presentation of information to stakeholders.